“Citizens of the Masonic Democracy”: The 18th Century Masonic Community in the Atlantic World and Beyond - Schwartz, Hans Jascha (2017)
This is an interview with Hans Schwartz, who recently completed a PhD at Clark University in Worcester, Massachusetts.  His dissertation, "Citizens of the Masonic Democracy":  The 18th Century Masonic Community in the Atlantic World and Beyond, views freemasonry from a trans-Atlantic perspective.